Cooperative insurance as an alternative to commercial insurance - Benchihab, Saloua; Boudliou, Salim (Journal of Human Sciences, 2021)
One of the contemporary issues in which financial art plays a leading role is the one of cooperative insurance as an alternative to conventional commercial insurance in covering various risks. Through this research paper, we will demonstrate the cardinal differences between the two as the interest for the cooperative insurance is getting higher after the big controversy over the legitimacy of the commercial insurance’s methods and after the its failure after the recent world’s crisis in which the world’s economies were hit. That period, which was characterized by vacancies, resulted in a need of an alternative solution that can assure safety and protect from unexpected risks; the things that cooperative insurance offers. Although the cooperative insurance system was successful, it still faces a number of challenges that stand in the way of its spread and evolution. Yet, despite all these challenges, there is a factor that promises a good future for this system.